Vemurafenib - Flaherty, Keith. T; Yasothan, Uma; Kirkpatrick, Peter (Nature reviews. Drug discovery, 2011)
In August 2011 vemurafenib (Zelboraf; Daiichi Sankyo/Roche), an inhibitor of BRAF kinase, was approved by the US Food and Drug Administration (FDA) for the treatment of patients with unresectable or metastatic melanoma with the BRAF V600E mutation.